Monitoring the health of wolves (Canis lupus): Integrating conservation and public health - Elisabetta Ferraro; Graziana Da Rold; Roberto Celva; Elisa Dalla Libera; Stefania Leopardi; Giulia Simonato; Paola De Benedictis; Nadia Cappai; Arianna Dissegna; Carlo Vittorio Citterio; Rudi Cassini; Federica Obber (PLoS ONE, 2026)
The grey wolf ( Canis lupus ) population is expanding in parts of Europe due to legal protection and favorable ecological conditions. As wolves increasingly move into urban and suburban areas, interactions with domestic dogs become more frequent, raising the risk of pathogen transmission and posing potential threats to both wolf conservation and public health. This study investigated the health status of wolves in the Foreste Casentinesi National Park (Italy) using non-invasive fecal sampling conducted between May 2019 and March 2020. Samples were genetically analyzed to identify individuals and then screened for viral pathogens, Canine Coronavirus and Parvovirus, using PCR, Sanger sequencing, and phylogenetic analysis. Parasitological examinations were performed using flotation techniques on whole samples, and real-time PCR targeting Echinococcus granulosus and E. multilocularis was conducted on selected samples. Of the 260 samples collected, genetic analysis identified 80 individual wolves belonging to 8 packs. Only one sample tested positive for Coronavirus (1.2%), and none for Parvovirus. The detected sequence clustered with strains previously reported in wolves and foxes in Italy. Copromicroscopy revealed a high prevalence of veterinary-relevant endoparasites, including Eucoleus spp. (90.0%), Sarcocystis spp. (42.5%), Taeniids (28.7%), and Ancylostomatids (26.2%). Trichuris vulpis , Toxocara canis , and coccidia showed prevalence rates below 2%. All 104 samples tested for E. granulosus or E. multilocularis were negative. These findings suggest that while wolves in the FCNP commonly harbor several canine parasites, their role in the transmission of zoonotic pathogens appears limited. Although phylogenetic data suggest that coronavirus strains tend to cluster within wildlife species, molecular data on domestic dogs remain scarce. Nonetheless, the high prevalence of shared parasites highlights the need for ongoing surveillance in both wild canids and domestic carnivores. As wolves increasingly inhabit human-dominated landscapes, understanding disease dynamics at the wildlife–domestic interface is essential for effective conservation and public health strategies.